2018
DOI: 10.4081/gh.2018.702
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the relationship between life expectancy and social determinants in a north-eastern region of Brazil, 2010-2017

Abstract: The process of population aging is a worldwide reality becoming a global public health challenge. Although population aging is especially noticeable in more developed regions, there has also been a significant advance in the quantity of elderly people in areas with unfavourable socioeconomic indicators, and a rapid growth in countries with a low level of economic development. This article presents an analysis based on spatial autocorrelation of the relationship between life expectancy and social determinants i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(25 citation statements)
references
References 21 publications
0
19
0
6
Order By: Relevance
“…In general, the areas with the lowest BR were usually economically developed, such as Shanghai and Beijing. The social welfare in these areas was also higher than that of other areas [39]. Moreover, areas with a lowest BR tended to have the fewest number of families members (NORPH) and the lowest total dependency ratio (TDR).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…In general, the areas with the lowest BR were usually economically developed, such as Shanghai and Beijing. The social welfare in these areas was also higher than that of other areas [39]. Moreover, areas with a lowest BR tended to have the fewest number of families members (NORPH) and the lowest total dependency ratio (TDR).…”
Section: Discussionmentioning
confidence: 86%
“…Many previous studies have shown that LE was mainly affected by economic factors [36,38,39]. For example, one study found that the main reason for the spatial distribution pattern of LE in China was the economy [40].…”
Section: Discussionmentioning
confidence: 99%
“…However, the older the age, the higher the proportion of underreporting in SINAN, with higher proportions for individuals over 50 years old. This result can be justified by the difficulty in diagnosing TB in elderly people (20)(21) and by existence of other comorbidities that mask TB occurrence, increasing underreporting cases and increasing difficulties of access to health services in this age group. Correlation between age and mortality from TB demonstrates the importance of early diagnosis in individuals older than 60 years (22) .…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, studying the influence of different factors on life expectancy has become a hot point of academic research [ 6 , 9 , 12 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 ]. In addition, scholars have been greatly interested in the influence of economic development on life expectancy.…”
Section: Literature Reviewmentioning
confidence: 99%